Improving Auditor Competence and Audit Quality Through Artificial Intelligence Moderation in Modern Financial Statement Digitization - Ferry Oktavianto Muis; Darmansyah Darmansyah; Sri Widyastuti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This research seeks to explore how the digitization of financial statements influences auditor competence and audit quality, alongside examining the moderating effect of Artificial Intelligence (AI) in this context. In the face of today's intricate business landscape, the auditing field must continually embrace new technologies to uphold precision and effectiveness. Employing a quantitative methodology, this study utilizes the Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis technique. Data were gathered through purposive sampling methods via questionnaires from 132 auditors employed at Public Accounting Firms (KAP) in the West Java area. The findings reveal that digitizing financial reports can substantially enhance both auditor competence and audit quality. Furthermore, AI usage has been shown to have a direct positive influence on these aspects. A key discovery of this study is that AI significantly moderates and bolsters the link between financial report digitization and auditor competence. However, AI does not significantly moderate the connection between digitization and audit quality. This suggests that audit quality is not solely reliant on technology but is also shaped by other elements such as human expertise, quality control, and adherence to audit standards. This study adds to the digital audit literature by emphasizing the significance of balanced technology integration in developing nations.